Political Moderation as a New Foundation in Indonesia: An Analysis of Deliberative Democracy Theory and Maqashid Shariah - Syahrain, Anggi; Sugitanata, Arif; Aminah, Siti (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2024)
This study explores the concept of political moderation in Indonesia, proposing it as a crucial approach to addressing the current political polarization. As one of the world's largest democracies, Indonesia faces challenges such as political polarization, disinformation, and the risk of social disintegration, exacerbated by regional elections and the dominance of political dynasties. This research introduces the concept of political moderation as a “new foundation” to balance ideological differences and ensure social stability. By analyzing this concept through Jürgen Habermas’s theory of Deliberative Democracy and Al-Shatibi’s Maqashid Shariah, the study integrates rational discourse and Islamic principles to highlight the importance of moderation in building an inclusive and sustainable democracy. The study employs a qualitative research methodology, utilizing primary data from selected books, journals, and online sources, and applies descriptive-analytical analysis to examine the implications of political moderation. The findings indicate that political moderation not only prevents the escalation of conflicts but also strengthens democratic institutions by promoting dialogue, tolerance, and respect for differing opinions. Additionally, political moderation aligns with Islamic values of justice and balance, contributing to the protection of religion, life, intellect, lineage, and property, as emphasized in Maqashid Shariah. The study concludes that political moderation is essential for maintaining national unity, promoting social justice, and ensuring the long-term stability and development of democracy in Indonesia.Abstrak: Penelitian ini mengeksplorasi konsep moderasi politik di Indonesia, mengusulkannya sebagai pendekatan penting untuk mengatasi polarisasi politik yang terjadi saat ini. Sebagai salah satu demokrasi terbesar di dunia, Indonesia menghadapi tantangan seperti polarisasi politik, disinformasi, dan risiko disintegrasi sosial, yang diperburuk oleh pemilihan daerah dan dominasi dinasti politik. Penelitian ini memperkenalkan konsep moderasi politik sebagai “fondasi baru” untuk menyeimbangkan perbedaan ideologi dan memastikan stabilitas sosial. Dengan menganalisis konsep ini melalui teori “Demokrasi Deliberatif Jürgen Habermas” dan “Maqashid Shariah Asy-Syatibi”, penelitian ini mengintegrasikan diskursus rasional dan prinsip-prinsip Islam untuk menyoroti pentingnya moderasi dalam membangun demokrasi yang inklusif dan berkelanjutan. Penelitian ini menggunakan jenis penelitian kualitatif dengan memanfaatkan data primer dari buku, jurnal, dan sumber online yang dipilih, serta menerapkan analisis deskriptif-analitis untuk mengkaji implikasi moderasi politik. Temuan menunjukkan bahwa moderasi politik tidak hanya mencegah eskalasi konflik tetapi juga memperkuat institusi demokrasi dengan mempromosikan dialog, toleransi, dan penghormatan terhadap perbedaan pendapat. Selain itu, moderasi politik sejalan dengan nilai-nilai Islam tentang keadilan dan keseimbangan, yang berkontribusi pada perlindungan agama, kehidupan, akal, keturunan, dan harta benda, sebagaimana ditekankan dalam Maqashid Shariah. Penelitian ini menyimpulkan bahwa moderasi politik sangat penting untuk menjaga kesatuan nasional, mempromosikan keadilan sosial, dan memastikan stabilitas serta perkembangan jangka panjang demokrasi di Indonesia.